Analisis Produktivitas Perbankan Syariah di Indonesia dalam Mengelola Dana Sosial - Ramadhan Rizky Putra; Sekarsukma Syifadhiya; Sekar Aji Widyastiti; Zulfikar Bagus Pambuko (JESI (Jurnal Ekonomi Syariah Indonesia), 2018)
Under the Law Number 21 of 2008 article 4 explains the obligation for Islamic banks in Indonesia to manage social funds, besides the funding and financing activities. This study aims to analyse the level of productivity of social funds at Islamic banks. Data analysis using Malmquist Productivity Index (MPI) technique on 8 BUS in 2013-2017. The input variables are the receipt of zakat funds and the charity funds, while the output variables are the use of zakat funds and the charity funds. The results of this study found that 5 BUS have managed social funds efficiently and three other BUS have inefficiency conditions. Furthermore, based on MPI analysis it is found that almost all Islamic Banks has increased productivity by 32.2% which is supported by 36.4% increase of TECHCH although EFFCH value decreased by -2.3%. It indicates that Islamic Banks in Indonesia is already using technology to improve its productivity. Furthermore, from 8 BUS that became the research object, only BRISyariah experienced a decrease in productivity.